Strategies and Implementation of Differentiated Instruction in Digital Teaching Materials: A Literature Review - Siti Nurlaili; Nurul Ainy; Miratunnisah Miratunnisah; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Teacher Education, 2024)
The rapid development of digital technology has transformed educational practices, particularly in the development of learning materials that are more adaptive to students’ diverse characteristics. Differences in abilities, interests, learning styles, and readiness require teachers to implement flexible and inclusive instructional strategies. One relevant approach is differentiated instruction integrated with digital learning materials. This study aims to analyze the strategies and implementation of differentiated instruction in digital teaching materials through a systematic literature review method. Data sources were collected from Google Scholar and Publish or Perish databases covering publications from 2015 to 2024. Of the 32 articles identified in the initial search, 16 articles met the inclusion criteria and were further analyzed. Data analysis was conducted using thematic analysis and narrative synthesis based on the types of digital materials, differentiation strategies, and their impacts on learning. The findings indicate that e-modules, digital flipbooks, Google Sites, Powtoon media, and Liveworksheet-based E-LKPD effectively support content, process, and product differentiation. Their implementation positively affects students’ learning motivation, engagement, creativity, and learning outcomes. Therefore, the integration of digital teaching materials and differentiated instruction can be considered an innovative strategy to create more personalized, interactive, and student-centered learning environments.